External assistance and Indian economic growth - Katz, S. Stanley (London : Asia Publishing House, 1968)
This book deals with the contribution made by external economic assistance to the growth and development achieved by the Indian economy during the period 1951-61, the decade of the First and the Second Indian Five Year Plans. The importance of foreign aid is reviewed in connection with domestic saving, income, and investment in the Indian economy. Within the theoretical framework of the Mahalanobis and Harrod-Domar model for economic development, the analysis of aid-development relationships and the basis of Indian development is carried out. The author sets out to demonstrate that economic progress has indeed been realized, that foreign aid has been well employed to fill the gaps in the domestic economy, and that foreign assistance has been an important element in the economic growth that has been achieved.
Includes index
Bibliography: p. 93-101.
usc 06/08/18
Loans
Keywords: Economic assistance; Economic history; India